2022
DOI: 10.1002/hpja.681
|View full text |Cite
|
Sign up to set email alerts
|

Are mothers under lunchbox pressure? An exploration of the experiences of Victorian mothers preparing lunchboxes for their children

Abstract: Issue Addressed: A healthy diet is particularly important during childhood. Research suggests that more than 95% of Australian primary school aged children do not eat a diet consistent with the Australian Dietary Guidelines, putting them at risk of poor health. Interventions to improve the quality of children's lunchboxes may help address this issue. However, there is limited understanding of the factors impacting lunchbox preparation.Methods: This study explored the experiences of 10 mothers of Victorian prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…This contrasts with commonly available ready-to-eat unhealthy lunchbox product items, which are convenient, food safe, require minimal labour and are acceptable to children ( Jabs and Devine, 2006 ; Bathgate and Begley, 2011 ; Rathi et al , 2018 ). Furthermore, many of these products feature child- or parent-directed marketing ( Watson et al , 2023 ). As a result, there is potential for the promotion of healthy lunchbox provision to reduce food costs, concurrently to increasing the availability and access to healthy, convenient and affordable food, to address the challenges faced by families.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with commonly available ready-to-eat unhealthy lunchbox product items, which are convenient, food safe, require minimal labour and are acceptable to children ( Jabs and Devine, 2006 ; Bathgate and Begley, 2011 ; Rathi et al , 2018 ). Furthermore, many of these products feature child- or parent-directed marketing ( Watson et al , 2023 ). As a result, there is potential for the promotion of healthy lunchbox provision to reduce food costs, concurrently to increasing the availability and access to healthy, convenient and affordable food, to address the challenges faced by families.…”
Section: Discussionmentioning
confidence: 99%
“…There is often also a stigma attached to lunch box contents, including feelings of embarrassment for children regarding what types of foods they bring, or in some cases how much food, if any at all ( Smith, 2021 ). This stigma is not exclusive to children with research indicating that Australian parents also feel stigma and embarrassment relating to their children’s lunch box contents and experience a range of barriers in providing school lunches including financial and time constraints and feel unsupported in providing appropriate food for their children ( Watson‐Mackie et al , 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that children's diets do not align with national recommendations in school settings where discretionary choices are commonly consumed (8) and home-packed lunches are shown to be lower in nutritional value than school-provided meals (9) . In addition, in a recent study, parents in Victoria (a state of Australia) identified barriers including cost and time to prepare a nutritious school lunchbox and felt that they were judged about the food they prepared (10) . Similarly, parents in Western Australia (another state of Australia) also reported that factors such as convenience, their child's preferences, cost and food safety concerns hindered their ability to include healthier options in their child's lunch box (11) .…”
mentioning
confidence: 99%